1990
DOI: 10.1159/000293229
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Contents in Cervical Secretions of Women with Chlamydial Cervicitis

Abstract: Contents of albumin, IgG, IgA and secretory IgA (S-IgA) were determined in secretions of 16 women with chlamydial cervicitis (study group) and 13 women with vulvovaginal candidiasis (control group). The amounts of respective protein in cervical secretions were higher among the women with chlamydial infection representing both an increased transudation and an increased local production of antibodies in the infected cervix. Specific chlamydial antibodies of IgG, IgA and S-IgA class were found significantly more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…105 A mucosal chlamydial infection elicits a humoral immune response with production of local and serum immunoglobulins of the IgA, IgG, and IgM classes." [106][107][108][109] In prospectively followed women, specific serum antibodies of the IgG class were detectable up to six years after an episode of acute salpingitis. '09 In one experimental study on guinea pigs, serum derived antibody was found to provide a partial protection against reinfection.…”
Section: Tubal Inflammationmentioning
confidence: 99%
“…105 A mucosal chlamydial infection elicits a humoral immune response with production of local and serum immunoglobulins of the IgA, IgG, and IgM classes." [106][107][108][109] In prospectively followed women, specific serum antibodies of the IgG class were detectable up to six years after an episode of acute salpingitis. '09 In one experimental study on guinea pigs, serum derived antibody was found to provide a partial protection against reinfection.…”
Section: Tubal Inflammationmentioning
confidence: 99%
“…The methods of normalizing cervicovaginal specimens are still a somewhat debatable topic in the field. In this study, we controlled the volume of endocervical and vaginal samples and did not normalize the levels of immune mediators based on concentrations of total protein or human albumin because of the influx of immune cells or proteins to the endocervix that occurs during C. trachomatis infection (Agrawal et al, 2007; Ficarra et al, 2008; Persson et al, 1990). Interestingly, we observed a decrease in HIV infectivity in endocervical secretions compared with CVL or vaginal secretions regardless of the treatment (Table 6), which could be a consequence of the overall higher concentrations of immune mediators including HIV inhibitory factors in the endocervix.…”
Section: Discussionmentioning
confidence: 99%